Joint Hypermobility in Paediatric Acute-Onset Neuropsychiatric Syndrome—A Preliminary Case-Control Study - Bejerot, Susanne; Hylén, Ulrika; Glans, Martin; Hesselmark, Eva; Humble, Mats B. (Frontiers in Psychiatry, 2021)
Background: Individuals with generalised joint hypermobility (GJH, present in 10%–20% of the general population) are at increased risk of being diagnosed with a range of psychiatric and rheumatological conditions. It is unknown whether Paediatric acute-onset neuropsychiatric syndrome (PANS), characterized by childhood onset obsessive-compulsive disorder or restricted eating and typically associated with several comorbid neuropsychiatric symptoms, is associated with GJH. It is also unknown whether extensive psychiatric comorbidity is associated with GJH. Method: This is a case–control study including 105 participants. We compared three groups: Individuals with PANS, individuals with other mental disorders and healthy controls. Joint mobility was assessed with the Beighton scoring system and psychiatric comorbidity with the MINI interview. Results: Hypermobility was similar across groups, and high rates of psychiatric comorbidity was not associated with higher Beighton scores. Conclusion: Although GJH is associated with several psychiatric conditions, such as ADHD and anxiety, this does not seem to be the case for PANS.